PENGARUH FASILITAS KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN (STUDI PADA CV. ZAM - ZAM JOMBANG) - Septian Ragil Anandita; Susi Indriyani; Wisnu Mahendri (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
This study aims to determine the effect of work facilities and communication on employee performance at CV. Zam – Zam Jombang. This study uses quantitative study methods. The sampling technique used is the Saturated Sampling (Census) in which all population members were sampled. So the sample in this study was 32 respondents. Data collection techniques using study instruments namely questionnaire. The instrument testing techniques are validity test and reliability test, data analysis technique uses the classical assumption test, and multiple linear regression analysis. The results showed that: 1) Work facilities have a significant effect on employee performance at CV. Zam – Zam Jombang, 2) Communication has no significant effect on employee performance on CV. Zam – Zam Jombang, 3) Simultaneous work and communication facilities have a significant effect on employee performance at CV. Zam – Zam Jombang.